2022
DOI: 10.3390/brainsci12050588
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Plasma Lysophosphatidic Acid Species in Patients with Alcohol and Cocaine Use Disorders

Abstract: Preclinical evidence suggests a main role of lysophosphatidic acid (LPA) signaling in drug addiction. Recently, we reported alterations in the plasma concentrations of LPA species in patients with alcohol use disorder (AUD). As there are sex differences in drug addiction, the main aim of the present study was to investigate whether relevant LPA species (16:0-LPA, 18:0-LPA, 18:1-LPA, 18:2-LPA and 20:4-LPA) were associated with sex and/or substance use disorder (SUD). This exploratory study was conducted in 214 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Among the potential candidates, several preclinical studies have suggested a potential role of lysophosphatidic acid (LPA) in drug addiction [ 12 15 ], and other studies have linked LPA signaling to substance use disorders (SUD) and its comorbidity [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the potential candidates, several preclinical studies have suggested a potential role of lysophosphatidic acid (LPA) in drug addiction [ 12 15 ], and other studies have linked LPA signaling to substance use disorders (SUD) and its comorbidity [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our group have suggested a potential role of LPA as a reliable biomarker for SUD, mainly in patients diagnosed with alcohol use disorder (AUD) [ 16 18 ]. Therefore, LPA could be a potential biomarker for mild cognitive impairment in abstinent patients with AUD [ 17 ], as well as plasma concentrations of ATX and LPA could be a preventive biomarker of liver disease in these patients with AUD [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this Special Issue aims to update our knowledge of the sexual and gender differences found in research into addictions and dual diagnosis. Thus, the articles included in this special issue cover both issues related to gender [ 1 , 7 ] and sex [ 6 , 8 , 9 ], patients using various substances [ 1 , 6 , 7 ] or others with specific substance use disorders (SUDs) [ 8 , 9 ], and including both issues related to addictions [ 9 ] and dual diagnosis [ 1 , 6 , 7 , 8 ].…”
mentioning
confidence: 99%
“…For their part, Flores-López et al (2002) [ 9 ] conducted an exploratory study to examine the plasma concentrations of lysophosphatidic acid (LPA, 1-acyl-2-hydroxy-sn-glycero-3-phosphate) species in women and men from a cohort of abstinent patients diagnosed with lifetime alcohol use disorder (AUD) and/or cocaine use disorder (CUD). The main results of their study were: (1) there are sex differences in LPA concentrations, which were higher in women; (2) there was a positive correlation between 16:0-LPA, 18:1-LPA, 18:2-LPA, 20:4-LPA, or total LPA concentrations and age in the SUD and control groups; (3) patients with SUD displayed lower 16:0-LPA, 18:2-LPA, and total LPA concentrations than healthy controls; (4) 16:0-LPA, 18:2-LPA, and total LPA concentrations were affected both by the diagnosis of a SUD and by sex, although there were no interactions between these two factors; and (5) the different species of LPA and total LPA concentrations were affected by the type of SUD: patients with CUD and AUD + CUD had lower LPA concentrations than the control or AUD groups.…”
mentioning
confidence: 99%